2006
DOI: 10.1080/17453670610046460
|View full text |Cite
|
Sign up to set email alerts
|

The native femoral sulcus as the guide for the medial/lateral position of the femoral component in knee arthroplasty: Normal patellar tracking in 690/700 knees—a prospective evaluation

Abstract: Interpretation The native femoral sulcus may be used as an effective and simple guide for the medial/lateral femoral component position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Mediolateral changes may result from a shift in the groove location due to one of several reasons: translation or axial rotation of the femoral component; changes in the soft-tissue tensions; or medialization or lateralization of the patellar component. Two recent studies have reported routine (i.e., unintended) medialization of the femoral groove due to arthroplasty [50,51]. Changes in spin were probably due to either the realignment of the leg as a result of the arthroplasty, or a change in the Q-angle based on the alignment of the components.…”
Section: Discussionmentioning
confidence: 99%
“…Mediolateral changes may result from a shift in the groove location due to one of several reasons: translation or axial rotation of the femoral component; changes in the soft-tissue tensions; or medialization or lateralization of the patellar component. Two recent studies have reported routine (i.e., unintended) medialization of the femoral groove due to arthroplasty [50,51]. Changes in spin were probably due to either the realignment of the leg as a result of the arthroplasty, or a change in the Q-angle based on the alignment of the components.…”
Section: Discussionmentioning
confidence: 99%
“…A myriad number of reference literature is devoted to its anatomy, sexual polymorphism, race and age transformations [2,4,7,9,11-17]. However, there is discrepancy as regards the angle meanings of the parameters and angle correlation to the linear characteristics of the femur.…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the angle meaning of the anteversion, according to numerous investigations [10-18], is roughly 74°. Also the literature data of the absolute meaning of the femur's head, other linear parameters, and transformation age are unequal [8,9,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Initially, there is a decrease in the exertion support and as a result some reduction of average absolute values of the transverse diaphysis was observed thus leading to a relative increase in the abovementioned parameters [26][27][28][29][30][31][32]. The changes in degenerative and dystrophic hip joint diseases are confirmed by statistically establishing a decrease in the transverse proximal epiphysis size (Table 2) that can be explained by the external rotation, which is a manifestation of forced rearrangement in alleviating pain.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the fact that the statistically established distinctions from the screening group can be viewed only in the angle between the femoral neck osseous trabeculae, the range of borders of the confidence intervals increased two times in each of the examined angulated parameters. Left-sided hip arthrosis localization revealed a more significant difference of this phenomenon in comparison with the right-sided process [1][2][3][4][5][6][7]13,[23][24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%